Dual Effects of Chinese Herbal Medicines on Angiogenesis in Cancer and Ischemic Stroke Treatments: Role of HIF-1 Network - Hong, Ming; Shi, Honglian; Wang, Ning; Tan, Hor-Yue; Wang, Qi; Feng, Yibin (Frontiers in Pharmacology, 2019)
HIF-1-induced angiogenesis has been involved in numerous pathological conditions, and it may be harmful or beneficial, depending on the types of diseases. Exploration of angiogenesis has sparked hopes in providing novel therapeutic approaches on multiple diseases with high mortality such as cancers and ischemic stroke. The HIF-1 pathway is considered to be a major regulator of angiogenesis. HIF-1 seems to be involved in vascular formation process by synergistic correlations with other proangiogenic factors in cancer and cerebrovascular diseases. The regulation of HIF-1-dependent angiogenesis involves the modulation of HIF-1 activity by regulating HIF-1α transcription and protein translation, HIF-1α DNA binding, HIF-1α and HIF-1β dimerization, as well as HIF-1 degradation. Traditional Chinese herbal medicines have a long history of clinical use in both cancer and stroke treatments in Asia. The objective of this review is to provide comprehensive insight on the effects of Chinese herbal medicines on angiogenesis by regulating HIF-1 pathways in both cancer and ischemic stroke.